PELATIHAN GURU PROFESIONAL DI MADRASAH TSANAWIYAH ISLAMIYAH GUNTING SAGA LABUHANBATU UTARA - Asrul Asrul; Syafaruddin Syafaruddin; Mursal Aziz; Walimsyah Sitorus (Jurnal Al-Fatih, 2021)
This research was conducted on community service through professional teacher training activities at MTs Islamiyah Gunting Saga aims to: (1) know the context of professional teacher training in MTs Islamiyah Gunting Saga, (2) know the input of professional teacher training in MTs Islamiyah Gunting Saga, (3) know the process of training professional teachers in MTs Islamiyah Gunting Saga, (4) know the professional teacher training products in MTs Islamiyah Gunting Saga. This research was conducted using cipp model program evaluation method (Context, input, process, and product). Data collection is done by interviewing techniques, observations and documentation. Guarantee the validity of data using triangulation (cross-examination), both triangulation between methods and between informants. While the analysis techniques are carried out with data reduction, data exposure and conclusion drawing. The findings of this study are four, namely: (1) analysis of the context of professional teacher training in MTs Islamiyah is the realization of the MOU between STIT Al Ittihadiyah Labuhanbatu Utara and Madrasah Islamiyah Gunting Saga, because there are still many MTs Islamiyah Gunting Saga teachers who have not PLPG / PPG, and the need for continuous teacher training after certification, (2) input analysis of professional teacher training of doctoral qualified trainers, providing teaching materials in the form of power points, there is the provision of insight expansion reading books, explaining the purpose of training, (3) analysis of the professional teacher training process there is the opening of the event, madrasah leadership speech, and STIT Al Ittihadiyah, forming a class format (U) to facilitate dialogue, there are assistant coaches, and moderators, there are, (4) analysis of training products attitude to training is very positive, the importance of completing the facilities / infrastructure of active learning, the expectation of increased teacher incentives , participants get certificates and expectations of continuous training.